How The Effect of Education After Level on COVID-19 Vaccination Status in the Community? - Sarah Patumona Manalu; Evawany Yunita Aritonang; Meutia Nurfahasdi; Silda Adi Rahayu; Ade Citra Nadhira (Tarbiyah : Jurnal Ilmiah Kependidikan, 2025)
The rapid global spread of COVID-19 requires practical prevention efforts, including vaccination. Public knowledge plays a crucial role in preventing transmission, and one factor influencing knowledge is education level. This study examines the relationship between educational attainment and COVID-19 vaccination status in Medan Tuntungan District. Using a cross-sectional design, the research involved 100 respondents from 68,000 individuals aged 18 and above. Data were collected through questionnaires and analyzed using univariate and bivariate methods. The results show no significant correlation between education level and COVID-19 vaccination status (p-value = 0.096). Several factors contribute to this, including widespread access to information through mass media and public campaigns and knowledge gained outside formal education. In conclusion, education level does not impact the COVID-19 vaccination status of the community in Medan Tuntungan District. The implication of these findings is the importance of a broader and more equitable communication strategy in vaccination campaigns, focusing on groups with high levels of education and covering groups with lower levels of education through easily accessible media.